Acculturation of Islamic Law and Local Culture in Marriage Customs of the Buol People: An Anthropological Perspective - Sumarno, Eko; Marzuki, Marzuki; Syarif Hasyim, Muhammad (INTERNATIONAL JOURNAL OF CONTEMPORARY ISLAMIC LAW AND SOCIETY, 2023)
The objective of this study is to examine acculturation of Islamic Law and Local culture in the Marriage Customs of the Buol People: This study examined two problems. First, how is the process of acculturation? Second, what acculturation occurs between Islamic law and local culture in the marriage customs of the Buol people?. This study used qualitative method with an empirical sociological legal research analysis approach. Data was gathered through in-depth interviews, direct observation, and participant observation, and physical equipment. The results of the study show that the process of acculturation occurs through power or politics, through trade, education, or da'wah and the arts, as well as through marriage and migration. Acculturation also occurs at every stage of the implementation of marriage customs among the Buol people, including through Mongolyokap, Molyako nikah or marraige proposal, Motanduan moposakis or determination and witnesses, Mopake bolre or decorating the bride's house, Mogundud nikah or delivering the requested property, Moponika or reading of Ijab Qabul (Islamic marriage contract), Monobvuwunggag or invalidating wudhu, Mongoliayondigi, Mopoalyom/Mogolya mongaano or wedding reception, Mosalyamat or small post-wedding party, and Mogolya mopolyong or sleeping at the groom's house. The forms of acculturation are substitution or addition of cultural elements, syncretism or an amalgamation of cultural factors, addition or combination of cultural elements, and deculturation or replacement of cultural aspects.